2017
DOI: 10.1055/s-0043-118666
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of TNF-α in the Development and Progression of Nonalcoholic Fatty Liver Disease in a Murine Model

Abstract: Previously, we have shown that the adipocyte-specific nuclear form of sterol regulatory element-binding protein-1c (nSREBP-1c) transgenic mice spontaneously developed hepatic lesions that are similar to those of human nonalcoholic steatohepatitis (NASH) with a concomitant elevation of plasma TNF-α. In this study, we analyzed the role of TNF-α in the progression of nonalcoholic fatty liver disease (NAFLD). We established a Tnf knockout nSREBP-1c transgenic mouse line. Glucose tolerance and liver histology were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 41 publications
4
85
0
2
Order By: Relevance
“…The supplementation of 5% CO could also elevate the circulated levels of tumor necrosis factor-alpha (TNF-α) in HF diet-fed rats ( Figure 3C). Kakino et al (2018) have suggested that TNF-α plays a pivotal role in the development and progression of NAFLD by the association with lipid metabolism and inflammation in the liver [18], which is consistent with our finding in the present study that diets supplemented with 5% CO may induce liver damage. Moreover, as shown in Figure 4, rats fed with HF diets for 8 weeks exhibit a significant increase in hepatic ( Figure 4A) and fecal ( Figure 4B) TC levels.…”
Section: Effects Of Hc Lc and Co On Hepatic And Fecal Lipid Responssupporting
confidence: 93%
“…The supplementation of 5% CO could also elevate the circulated levels of tumor necrosis factor-alpha (TNF-α) in HF diet-fed rats ( Figure 3C). Kakino et al (2018) have suggested that TNF-α plays a pivotal role in the development and progression of NAFLD by the association with lipid metabolism and inflammation in the liver [18], which is consistent with our finding in the present study that diets supplemented with 5% CO may induce liver damage. Moreover, as shown in Figure 4, rats fed with HF diets for 8 weeks exhibit a significant increase in hepatic ( Figure 4A) and fecal ( Figure 4B) TC levels.…”
Section: Effects Of Hc Lc and Co On Hepatic And Fecal Lipid Responssupporting
confidence: 93%
“…Thus, it is not surprising that TNF sensing by hepatocytes promotes hepatocyte cell death and hepatocyte proliferation (67), and as such directly contributes to NAFLD pathogenesis (68). Further, deletion of TNF in experimental mouse models of NAFLD correlates with decreased steatosis, fibrosis and improved glucose tolerance (69).…”
Section: Macrophages and Proinflammatory Cytokine Productionmentioning
confidence: 99%
“…36 In the rat models, previous experiments implied a pivot role of TNF-α in the pathogenesis of NASH. 11 Administration of infliximab could reverse diet-induced hepatic steatosis in rats. 17 18 The sonographic stage of NAFLD also correlated with serum levels of TNF-α in individuals with morbid obesity.…”
Section: Discussionmentioning
confidence: 99%